Representation at CCMA tribunal: still a vexed issue - Hendricks, Clive Sinclair (Department of Commercial Law, 2023)
Legal representatives play a prominent role in most court proceedings. There are however, different perspectives on the role they should play in tribunals charged with the task of labour dispute resolution. With the enactment of the Labour Relations Act 66 of 1995 (hereinafter 'LRA') Minister Tito Mboweni, then the Minister of Labour, repeatedly commented that the Commission for Conciliation, Mediation and Arbitration (hereinafter 'CCMA') were structured in such a manner that it would not be necessary for employees and employers to be represented by legal representatives as they would be able to represent their cases themselves. While the idea is that people should not need legal representation before tribunals because of their supposed informal atmosphere, in practice many parties to tribunal hearings are ordinary citizens who are not skilled at presenting fact and argument and are often inarticulate. The absence of a requirement for formal pleadings and complicated referral procedures has, it seems, however ensured that literacy and a lack of skill and resources do not cause an entry barrier to the system. According to the explanatory memorandum which accompanied the LRA, a key objective of the legislation was to address the perceived shortcomings of the previous system. In essence the system was considered to be: costly, time consuming, technical, complex, inaccessible, legalistic, illegitimate, and not delivering industrial justice. With very little exceptions, a common theme in the explanatory memorandum and labour court judgments is that legal representatives have been responsible for tribunals operating in unnecessarily complex, time consuming, formal and costly ways. The aim of the current study was to investigate the issue of legal representation of parties. in unfair dismissal disputes, now the most common of employment disputes. The paper · evaluated the nature of representation and endeavoured to weigh up the pros and cons of allowing parties in dismissal disputes to be represented by legal practitioners or other categories of representatives. To that end, the author provided a review of the arguments for and against allowing legal representation in cases concerning dismissals. In investigating the aforementioned, the author also evaluated whether there is indeed substance in the criticisms leveled against legal representatives engaged in alternative dispute resolution (hereinafter 'ADR').